2009
DOI: 10.14310/horm.2002.1246
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid volume, selenium levels and nutritional habits in a rural region in Albania

Abstract: OBJECTIVE Environmental factors are involved in goiter development. An increased number of goitrous patients were identified among outpatients in Gyrocaster, a mountainous region in Southwestern Albania. We examined possible associations of thyroid enlargement with nutritional factors. DESIGN 112 consecutive patients, 104 females, aged 52.8 ±12.1 (mean±SD), who either were taking thyroxine (n=27) or were suspected to have thyroid disease were examined. Thyroid parameters and nutritional habits were recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…In the present study, serum Se concentrations from a population of elderly healthy Swedes were low (~ 67.1 μg/l) compared with the reported Se levels in the United States 25 , 26 and also relatively low in comparison with values in other regions in Europe. 18 , 19 , 27 , 28 , 29 , 30 , 31 , 32 The difference in concentrations between smokers and non-smokers in the present study was not significant, which may be an effect of the small size of the smoking group ( n =40; 9.0%), as some studies have found decreased levels in current smokers. 33 , 19 However, there are also studies where such an association has not been found.…”
Section: Discussioncontrasting
confidence: 82%
“…In the present study, serum Se concentrations from a population of elderly healthy Swedes were low (~ 67.1 μg/l) compared with the reported Se levels in the United States 25 , 26 and also relatively low in comparison with values in other regions in Europe. 18 , 19 , 27 , 28 , 29 , 30 , 31 , 32 The difference in concentrations between smokers and non-smokers in the present study was not significant, which may be an effect of the small size of the smoking group ( n =40; 9.0%), as some studies have found decreased levels in current smokers. 33 , 19 However, there are also studies where such an association has not been found.…”
Section: Discussioncontrasting
confidence: 82%
“…John et al [12] found that when the intake of selenium was sufficient, there was no correlation between goiter and serum selenium levels even in a mild iodine-deficient area. A study in school-age children in Turkey [22] with moderate iodine deficiency, found that mean selenium was 50 μg/L, a relatively low level, and serum selenium concentration was not associated with thyroid volume, thyroid goiter, or THS levels.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off levels were derived from the mean (+2 SD) thyroid volume in 597 subjects (315 males and 282 females) without thyroid dysfunction, without a previous thyroid disease, without a family history of thyroid disease, without positive thyroid autoantibodies, and without goiter or nodules on ultrasonography [12]. …”
Section: Methodsmentioning
confidence: 99%
“…9,32 In adults with Se deficiency, an increased propensity for neoplastic diseases was detected (particularly for malignant tumours of prostate, breast and colon), certain thyroid diseases, neuropsychiatric disturbances and disturbance of fertility proved to be more frequent. 12,[33][34][35][36] A lowered serum Se concentration was detected in women with frequent abortions, in men with diagnosis of oligospermia. 11 In recent years, deficiency of Se was found to be significant in pathogenesis of circulatory diseases.…”
Section: Discussionmentioning
confidence: 99%